Metabolic Alterations in Obstructive Jaundice: Effect of Duration of Jaundice and Bile-Duct Decompression. Issue 1 (1991) - Younes, R. N.; Vydelingum, N. A.; Derooij, P.; Scognamiglio, F.; Andrade, L.; Posner, M. C.; Brennan, M. F.
Abstract : We examined the effect of prolonged bile duct obstruction, and subsequent biliary decompression, on biochemical and metabolic parameters, using a reversible jaundice model in male Fischer 344 rats. The animals were studied after biliary obstruction for varying periods (4 days, one week, and two weeks) and following decompression. They were sacrificed one or two weeks following decompression. All the rats were compared to sham operated, pair-fed, controls. Obstructive jaundice rapidly increased bilirubin, liver enzymes, serum free fatty acid, and triglyceride levels. Glucose levels were significantly decreased in the jaundice rats compared to their pair-fed controls. Only after two weeks of jaundice was significant hypoalbuminemia observed. Following decompression, all biochemical and metabolic values gradually returned to normal levels, except for albumin. Hypoalbuminemia was not reversed within the two-week post-decompression period. The rats jaundiced for two weeks had significantly higher mortality, compared to the other groups. We conclude that prolonged jaundice adversely affects the metabolic capacity of the rats, with albumin concentration being markedly decreased, and that biliary decompression could not reverse completely all the alterations seen with cholestasis, especially following two weeks of bile duct obstruction.